A genome-wide association study of bronchodilator response in participants of European and African ancestry from six independent cohorts. Issue 2 (27th June 2022) - Gereige, Jessica D.; Xu, Hanfei; Ortega, Victor E.; Cho, Michael H.; Liu, Ming; Sakornsakolpat, Phuwanat; Silverman, Edwin K.; Beaty, Terri H.; Miller, Bruce E.; Bakke, Per; Gulsvik, Amund; Hersh, Craig P.; et al.
Introduction: Bronchodilator response (BDR) is a measurement of acute bronchodilation in response to short-acting β2-agonists, with a heritability between 10 and 40%. Identifying genetic variants associated with BDR may lead to a better understanding of its complex pathophysiology. Methods: We performed a genome-wide association study (GWAS) of BDR in six adult cohorts with participants of European ancestry (EA) and African ancestry (AA) including community cohorts and cohorts ascertained on the basis of obstructive pulmonary disease. Validation analysis was carried out in two paediatric asthma cohorts. Results: A total of 10 623 EA and 3597 AA participants were included in the analyses. No single nucleotide polymorphism (SNP) was associated with BDR at the conventional genome-wide significance threshold (p<5×10 −8 ). Performing fine mapping and using a threshold of p<5×10 −6 to identify suggestive variants of interest, we identified three SNPs with possible biological relevance: rs35870000 (within FREM1 ), which may be involved in IgE- and IL5-induced changes in airway smooth muscle cell responsiveness; rs10426116 (within ZNF284 ), a zinc finger protein, which has been implicated in asthma and BDR previously; and rs4782614 (near ATP2C2 ), involved in calcium transmembrane transport. Validation in paediatric cohorts yielded no significant SNPs, possibly due to age–genotype interaction effects. Conclusion: Ancestry-stratified and ancestry-combined GWAS meta-analyses of over 14 000 participants did not identify genetic variants associated with BDR at the genome-wide significance threshold, although a less stringent threshold identified three variants showing suggestive evidence of association. A common definition and protocol for measuring BDR in research may improve future efforts to identify variants associated with BDR. While no genetic variant reached genome-wide significance in a multiethnic GWAS of bronchodilator response, genes of interest include FREM1, ZNF284 and ATP2C2 https://bit.ly/3PcOnUe